Development of precipitation intensity-duration-frequency curves for litani river basin - Lebanon - Obeid, Hilal; El Kholy, Mohamad (International Journal of Engineering and Technology, 2021)
Most countries in the Middle East region lack the availability of rainfall data and relationships for the rainfall durations and frequencies. In this study, the daily rainfall data collected from Lebanese Agricultural Research Institute and Beirut Airport Weather Forecast for five stations in Litani River Basin-Lebanon over a period of twenty-three years are analyzed. SCS Type II rainfall distribution was adopted for short duration intervals. Gumbel, Normal, and the Log Pearson Type III distributions are used to develop the relationship between the rainfall intensity, storm duration, and return periods. Chi-Square test is used to confirm the suitability of the fitted distributions. Results obtained using Log Pearson and Gumbel distributions are very close and are more applicable compared to that of the Normal Distribution. Also, results show that IDF equations of Kimijima and Sherman may fit well at all stations.Â Â Â